Awqaf System for Sustainable WASH Services in Developing Countries: A Viable Alternative to Donor-Dependent Models - Safia Minhaj (Badan Wakaf Indonesia, 2025)
Abstract: Access to safe drinking water, adequate sewerage systems, andreliable hygiene services (WASH) infrastructure is fundamental to publichealth and socio-economic development. In many developing countries likePakistan, however, WASH services are often underfunded and heavilyreliant on external donors. Financing from the funding agencies ismounting the amount of public debt in these countries and enhancing thesize of already existing twin deficit. This paper proposes the utilization of asystem of Awqaf (Islamic endowment model) as a sustainable andcommunity-driven alternative to external loans or aid. It also explores theviability of integrating a revitalized system of Awqaf as a sustainablefinancing and governance model for WASH infrastructure. Unlike donorbased models, the Awqaf approach is rooted in local culture, encouragescommunity ownership, and can provide long-term, debt-free fundingthrough self-sustaining endowment mechanisms. The theoreticalframework of the study links financial innovation (waqf-based instrumentssuch as cash waqf, waqf sukuk, and blended waqf–PPP models) withfinancial inclusion, arguing that this connection can strengthen servicesustainability and fiscal stability. This policy research compares Awqafbased initiatives with conventional donor-funded WASH projects usingselected case studies, and assesses their performance in terms ofsustainability, equity, cost-effectiveness, and institutional resilience.Findings suggest that, with proper legal and administrative frameworks, theAwqaf model can complement or, in some contexts, substituteinternational funding while strengthening local governance structures. Thissystem could play a pivotal role in achieving sustainable development goalsrelated to water and sanitation in the Global South.Keywords: waqf, WASH, sustainable development, donor dependency.